Inhalant Dependence and its Medical Consequences - Mehmet Hamid Boztaş (Psikiyatride Güncel Yaklaşımlar, 2010)
The term of inhalants is used for matters easily vapors. Inhalants are preferred for rapid, positive reinforcement and mild high effects. Products including inhalants are cheap, accessible, legal substances and are prevalently used in community. The prevalence of inhalant use in secondary schools in Turkey is about 5.1%. Inhalant substance dependence is generally observed within 14-15 age group. Age at first use could be as low as 5 to 6 years of age. Substance dependence is more probable in adults working in substance existing places. Inhalant usage is common in disadvantaged groups, children living in street, people with history of crimes, prison, depression, suicide, antisocial attitudes and conflict of family, history of abuse, violence and any other drug dependence and isolated populations. Inhalants are absorbed from lungs, after performing their quick and short effect metabolized by cytochrom P450 enzyme system except inhalant nitrites group which has a depressing effect like alcohol. In chronic use general atrophy, ventricular dilatation and wide sulcus were shown in cerebrum, cerebellum and pons by monitoring brain. Defects are mostly in periventricular, subcortical regions and in white matter. Demyelinization, hyperintensity, callosal slimming and wearing off in white and gray matter margins was also found. Ravages of brain shown by brain monitorisation are more and serious in inhalant dependence than in other dependences. It is important to decrease use of inhalants. Different approaches should be used for subcultures and groups in prevention. Prohibiting all the matters including inhalant is not practical as there are too many substances including inhalants. Etiquettes showing harmful materials can be used but this approach can also lead the children and adolescents recognize these substances easily.. Despite determintal effects of inhalant dependence, there are not yet sufficient number of studies conducted on prevention and treatment. Future studies should focus on these issues. As majority of inhalant users are adolescents who are living in streets, identification of these groups in detail could be beneficial for planning and implementation of future interventions.